2019
DOI: 10.1007/s10815-018-1395-y
|View full text |Cite
|
Sign up to set email alerts
|

Health care provider perceptions of fertility preservation barriers and challenges with transgender patients and families: qualitative responses to an international survey

Abstract: Purpose To examine provider perceptions of practice behaviors and barriers related to fertility counseling, fertility preservation, and family building among transgender patients. Methods Participants were medical and mental health professionals who treat adult and youth transgender patients. Recruitment occurred online and in person, via professional listservs for transgender professionals, conferences, and gender clinics. From August-November 2017, 110 participants representing nine countries responded to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 60 publications
0
52
0
Order By: Relevance
“…These men are not alone. A recent international survey of fertility preservation providers in nine countries (Tishelman et al, 2019) showed that oocyte cryopreservation is increasing in the transgender community, as transgender men work to preserve their potential for future fatherhood.…”
Section: Extended Questsmentioning
confidence: 99%
“…These men are not alone. A recent international survey of fertility preservation providers in nine countries (Tishelman et al, 2019) showed that oocyte cryopreservation is increasing in the transgender community, as transgender men work to preserve their potential for future fatherhood.…”
Section: Extended Questsmentioning
confidence: 99%
“…7 Unfortunately, physicians' selfreported limited knowledge of fertility preservation for transgender patients was recently identified as a barrier to care. 20 To better support medical providers, a ''decision tool web portal'' that houses up-to-date literature and helps providers tailor patient discussions can be developed similar to what has been done for 202 KATABI ET AL.…”
Section: The Right To Utilize Fertility Preservationmentioning
confidence: 99%
“…150 Although there are many options for fertility preservation in trans people, 151 many trans people still consider fertility the price to pay for transition 152 and cost remains an incredible barrier to undergoing fertility preservation. 153 For TW who underwent pubertal suppression, fertility preservation was often not possible at pubertal developmental Tanner 2 stage. 147 Adolescents are offered the choice of postponing pubertal suppression in order to proceed with fertility preservation or to initiate pubertal suppression at Tanner 2 and to interrupt the therapy for fertility preservation prior to initiation of GAHT.…”
Section: Part 3: Risks Associated With Gahtmentioning
confidence: 99%